Using Word Wall Game to Improve Students’ Writing Ability at the Second Grade Students of Junior High School - Dwi, Veloni Ova; Kumala, Sari Rosi; Rahma, Dania; Suparmi (IPI Garut Press, 2024)
This study aimed to determine whether the use of the Word Wall game can improve students' writing skills in learning English at 7th State Junior High School in Padang. The population and sample of this research were 33 students of class VIII. The type of research was quantitative. The method used was a pre-experimental method design, with one group. The data collection technique used in this research was tests, including a pre-test and post-test. The results of the data showed that the average student score on the post- test was (82,5), higher than the average score on the pre- test (39,75). From the t-test, the study showed that the t- test value (29,14) is higher than the t-table (1,697) at a significance level of 0.05 with degrees of freedom (df) = 32. This result meant that there was a significant difference. This indicated that the alternative hypothesis (H1) is accepted and the null hypothesis (Ho) is rejected. Hence, it can be concluded that the use of Word Wall significantly improves students' writing skills.